Determination of Campus Image, Promotion and Education Costs on College Selection Decisions, Through Student Satisfaction As An Intervening Variable At Batam University - Dewi Agustina; Chablullah Wibisono; Gita Indrawan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to determine the direct and indirect effect of campus image, promotion, education costs on college seletion decisions through student satisfaction as an intervening variable at Batam University. This type of research uses quantitative research methods with primary and secondary data sources. The population in this study were all active batam university students until 2024, namely 2703 students. By using the Slovin formula, the sample size is minimized, so the number of samples (n) in this study was 190.35 people rounded up to 190 people. This research uses Smart-Pls as a data processing tool. The results of this study indicate Campus image has a significant positive effect on student satisfaction in choosing Batam University, therefore Hypothesis 1 in this study is accepted. Promotion has a positive but insignificant effect on student satisfaction choosing at the University of Batam, therefore Hypothesis 2 in this study is rejected. Education costs have a significant positive effect on student satisfaction choosing Batam University, therefore Hypothesis 3 in this study is accepted. Campus image has a positive but insignificant effect on the selection decision at the University of Batam, therefore Hypothesis 4 in this study is rejected. Promotion has a positive but insignificant effect on the selection decision at the University of Batam, therefore Hypothesis 5 in this study is rejected. Education costs have a positive but insignificant effect on selection decisions at Batam University, therefore Hypothesis 6 in this study is rejected. Student satisfaction has a significant positive effect on selection decisions at Batam University, therefore Hypothesis 7 in this study is accepted. Campus image has a positive but insignificant effect on college selection decisions through student satisfaction at Batam University, therefore Hypothesis 8 in this study is rejected. Promotion has a significant positive effect on college selection decisions through student satisfaction at the University of Batam, therefore Hypothesis 9 in this study is accepted. Education costs have a positive but insignificant effect on college selection decisions through student satisfaction at Batam University, therefore Hypothesis 10 in this study is rejected.